Recent Applications of Ammonium Ylide Based [2,3]-Sigmatropic and [1,2]-Stevens Rearrangements To Transform Amines into Natural Products - Schwartz, Zachary; Valiton, Chelsea; Lovasz, Myles; Roberts, Andrew G. (Synthesis, 2023)
Ammonium ylide based [2,3]-sigmatropic and [1,2]-Stevens rearrangements enable the transformation of tertiary amines into rearranged and functionalized intermediates en route to many polycyclic natural product targets. Herein, we summarize recent applications of these rearrangement reactions in formal and total synthesis endeavors while highlighting innovative improvements to these transforms.1 Introduction2 Ammonium Ylide Based [2,3]-Sigmatropic Rearrangements in Natural Product Synthesis2.1 (–)-Cephalotaxine2.2 (±)-Amathaspiramide F2.3 (–)-Cephalezomine G and Its C3 Epimer2.4 (±)-Strictamine2.5 (–)-Doxycycline3 [1,2]-Stevens Rearrangements Toward Natural Products3.1 Ring-Expanding [1,2]-Stevens Rearrangements en route to (±)-Tylophorine, (±)-7-Methoxycryptopleurine, and (±)-Xylopinine3.2 Enantioselective Synthesis of Iboga Alkaloids and (+)-Vinblastine4 Selected Methodology4.1 Ammonium Ylide Based [2,3]-Sigmatropic Rearrangements To Form Natural Product Cores4.2 Cascade Reactions Involving [1,2]-Stevens Rearrangement/ Hofmann-Type Elimination Events5 Conclusions
Keywords: ammonium ylides; [1,2]-Stevens rearrangement; [2,3]-sigmatropic rearrangement; [2,3]-Stevens rearrangement; natural products; alkaloids